2010
DOI: 10.1007/s00421-010-1753-7
|View full text |Cite
|
Sign up to set email alerts
|

Training in the fasted state facilitates re-activation of eEF2 activity during recovery from endurance exercise

Abstract: Nutrition is an important co-factor in exerciseinduced training adaptations in muscle. We compared the effect of 6 weeks endurance training (3 days/week, 1-2 h at 75% VO 2peak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…We did not evaluate the acute effects of exercise, but analyses on resting muscle biopsies showed that the 6-wk SIT period up-regulated neither muscle AMPK total protein content nor AMPK phosphorylation status (Èactivity). Studies in our (33,34) and other laboratories (27) have previously Values are presented as mean T SEM observations during the first (week 1) and the last week (week 6) of the training period involving 30-s intermittent sprints in either normoxia (NOR, n = 9; F i O 2 , 20.9%) or hypoxia (HYP, n = 10; F i O 2 , 14.5%). The number of sprints per session was increased from four in week 1 to nine in week 6.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate the acute effects of exercise, but analyses on resting muscle biopsies showed that the 6-wk SIT period up-regulated neither muscle AMPK total protein content nor AMPK phosphorylation status (Èactivity). Studies in our (33,34) and other laboratories (27) have previously Values are presented as mean T SEM observations during the first (week 1) and the last week (week 6) of the training period involving 30-s intermittent sprints in either normoxia (NOR, n = 9; F i O 2 , 20.9%) or hypoxia (HYP, n = 10; F i O 2 , 14.5%). The number of sprints per session was increased from four in week 1 to nine in week 6.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms are likely to be different from training with low glycogen. Van Proeyen et al [36] found no differences in AMPK in subjects training in the fasted vs. fed state, but did observe differences in post-exercise eukaryotic elongation factor 2 phosphorylation (elevated after carbohydrate feeding but not after fasting). De Bock et al [35] showed that exercise in the fasted state facilitated intramuscular fat use during exercise and improved glycogen resynthesis [35].…”
Section: Nutritional Training: Specific Goals Require Specific Methodsmentioning
confidence: 99%
“…The synergistic effect of endurance exercise on AMPK phosphorylation observed in food‐deprived rodents (16) was initially also observed in humans, accompanied by a clearly boosted shift toward increased fatty acid over carbohydrate oxidation in vastus lateralis muscle (17). In a study of lean human subjects by the same authors, the increase in AMPK phosphorylation observed by exercise was not further increased by fasting (18). Instead, in this study, it was observed that fasting stimulates, after endurance exercise, dephosphorylation of eukaryotic elongation factor‐2, which favors rapid reinitiation of muscle protein translation and repair (18).…”
Section: Combining Fasting/food Withdrawal With Endurance Exercise Mamentioning
confidence: 98%
“…In a study of lean human subjects by the same authors, the increase in AMPK phosphorylation observed by exercise was not further increased by fasting (18). Instead, in this study, it was observed that fasting stimulates, after endurance exercise, dephosphorylation of eukaryotic elongation factor‐2, which favors rapid reinitiation of muscle protein translation and repair (18). Whereas endurance exercise in humans per se has been shown to increase autophagy (75, 92), the above data suggest that endurance exercise in fasting conditions may circumvent muscle autophagy in humans and shift the balance toward repair and maintenance of mass of existing muscle structures over protein degradation within muscle fibers.…”
Section: Combining Fasting/food Withdrawal With Endurance Exercise Mamentioning
confidence: 98%
See 1 more Smart Citation